COVID-19 research spread in Indonesia on social media - La Tarifu; Joko Joko; Cecep Ibrahim; Rahmat Fadhli; Sri Hartinah (Berkala Ilmu Perpustakaan dan Informasi, 2022)
Introduction. The purpose of this study is to determine the impact of Indonesian COVID-19 research. One of them is productive author, productive citations, the most popular social media to disseminate research results, the most popular articles on social media, mapping or distribution of research results visualization, and the correlation of social media data with citations. Data Collection Method. The research data was taken from the Scopus database and this research use method Bibliometric, Altmetric, Scientometric, and linear regression tests. Data Analysis. The data of the study was analyzed using program (altmetric.com), VOSViewer and SPSS software. Result and Discussion. Pranata, R. was the productive author in producing Indonesian COVID-19 research. The University of Indonesia is the most productive institution. The study "Clinical, laboratory, and imaging features of COVID-19: A systematic review and meta-analysis" received the most citations and shares on social media. Mendeley is the most popular social media platform for disseminating research. Conclusion. Based on the above findings, the spread of COVID-19 research in Indonesia on the most popular social media is mendeley 17.701, followed by Twitter 2.971 and news mentions 177. According to linear regression tests, mendeley is social media platform with a high correlation value of 0.814.